PENGARUH PEMBERIAN RANSUM YANG BERBEDA TERHADAP KUALITAS PUTIH TELUR - Suarda, Andi (Teknosains: Media Informasi Sains dan Teknologi, 2015)
This research aimed to get an idea of the extent to which different rations pemberian influence on the quality of the egg white. Material used in this research is the production phase of the laying hens numbered 48 animals, aged nine months, and the strains of "super Harco CP 306" derived from PT.Charoen Pokhpan Jaya Farm, Jakarta. The chickens kept in 24 cages each measuring 1 × 0.5 × 1m made from bamboo which parts of 2 cm in width are arranged with a distance of 1.5 to 2 cm. litter used consisted of rice husk and slats. Placement of chickens in cages is done randomly, in which each cages filled two chickens were equipped each one fruit places to eat and drink. Places to eat and drink in a cage placed in such a way, so that each chicken gets an equal opportunity to eat and drink. Feeding is done ad-libitum. Cow rumen contents obtained from Slaughterhouse, Makassar. The experimental design used was completely randomized design 4 × 2 factorial pattern with three replications (Steel and Torrie, 1980). The first factor is a kind of ransom, which consists of R-1 is the ration without using flour content of cow's rumen, R-2 is a diet containing 2.5% starch content of cattle rumen, R-3 is a ransom containing 5% starch content of cattle rumen, R-4 is a ransom containing 7.5% starch content of cow's rumen. he second factor is the type of litter consisting of Rice Husk and slats. The parameters measured in this study is the eggshell thickness, eggshell weight. Eggshell thickness measurement done at three locations using a micrometer. Subtract the weight obtained by the weight at the time of solving the weight of albumen (egg white) and yolk weight. Results showed that: 1) use of flour content of cow rumen to the level of 7.5% in the diet of laying hens showed no significant effect on the weight of albumen (egg white), 2) the interaction between the type of feed and litter used do not show the real effect against the weight of albumen (egg white).